Synthesis, characterization and antibacterial activity of poly(N-vinylimidazole) grafted chitosan - Caner, Hamit; Yilmaz, Elvan; Yimaz, Osman (Elsevier Sci Ltd, 2007)
Poly(N-vinylimidazole) has been grafted onto chitosan in dilute acetic acid solution via ceric ion initiation. The effect of the amounts of N-vinylimidazole monomer, cerium(IV) ammonium nitrate initiator, chitosan substrate, as well as chitosan molecular weight, temperature and reaction time on the grafting yield has been investigated. The maximum grafting yield achieved was 140% in 1.0% (w/V) chitosan solution at 0.2 M N-vinylimidazole, 70 degrees C within 3 It under nitrogen atmosphere. The grafted products were characterized by gravimetric methods, FTIR and DSC. Grafted chitosans with lower grafting yields less than 108% were completely soluble in neutral water. Products with higher % grafting values swell in aqueous solution. Grafted products have improved antibacterial activity. (C) 2007 Published by Elsevier Ltd.
Keywords: 1-vinylimidazole; CAN; cerium; enzymes; water-soluble polymers